Pengaruh tutor sebaya dan motivasi guru terhadap hasil belajar siswa pada SD Negeri 104 Palembang - Lestari, Susi; Putra, Alhadi Yan; Indrawati, Sri Wahyu (Media Manajemen Pendidikan, 2024)
The purpose of this study was to determine the effect of peer tutors and teacher motivation on student learning outcomes at State Elementary School 104 Palembang. The sample size taken was 60 students of State Elementary School 104 Palembang City. The sampling technique was purposive sampling, where the respondents taken were some of the sixth grade students of SD 104 Palembang City. Data collection was carried out by distributing questionnaires using a 5 point likert scale to measure 90 statement items. The analysis technique used was simple and multiple linear regression analysis. The results showed that 1). there is an influence of peer tutors on student learning outcomes 2). there is an influence of teacher motivation on student learning outcomes 3). there is an influence of peer tutors and teacher motivation on student learning outcomes.